2020
DOI: 10.1111/soin.12381
|View full text |Cite
|
Sign up to set email alerts
|

“We Need to Do Something About This”: Children and Youth’s Post‐Disaster Views on Climate Change and Environmental Crisis

Abstract: Research is increasingly uncovering the many ways that individuals affected by disasters change their environmental views in response to their direct experience of such catastrophic events. There is a growing body of research that focuses on adults’ environmental views, revealing that they often remain complacent toward environmental problems even after experiencing a disaster. However, very little research examines whether and to what extent children and youth’s environmental views shift and change after expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 51 publications
(89 reference statements)
1
19
0
Order By: Relevance
“…In these fossil fuel dependent communities, it can be difficult to speak about the environment and about climate change. Residents fear ostracization and exclusion (Evans and Garvin 2009;Davidson 2018) as the larger fossil-fuel dependent community refuses to tolerate dissent or opposing views, though speaking out against the hegemony of fossil fuels is often undertaken by women (Bell 2013;Bell and Braun 2010) and by children (McDonald-Harker, Bassi, and Haney 2021), those most negatively affected by the industry and with fewer direct economic ties to the industry.…”
Section: Fossil Fuel Communities and Climate Change Beliefsmentioning
confidence: 99%
See 1 more Smart Citation
“…In these fossil fuel dependent communities, it can be difficult to speak about the environment and about climate change. Residents fear ostracization and exclusion (Evans and Garvin 2009;Davidson 2018) as the larger fossil-fuel dependent community refuses to tolerate dissent or opposing views, though speaking out against the hegemony of fossil fuels is often undertaken by women (Bell 2013;Bell and Braun 2010) and by children (McDonald-Harker, Bassi, and Haney 2021), those most negatively affected by the industry and with fewer direct economic ties to the industry.…”
Section: Fossil Fuel Communities and Climate Change Beliefsmentioning
confidence: 99%
“…At the same time, Milnes and Haney (2017) show how fossil fuel dependence explains men's post-disaster environmental complacency, and they find that women are more likely to embrace environmentalism after disaster. The ways dependence manifests in environmental views is made evident by McDonald-Harker, Bassi, and Haney (2021), who studied disaster-affected children in Alberta. Despite living in a community where many people are dependent on fossil fuels, children (even many whose parents worked in oil) spoke emotionally and persuasively about the climate crisis and the need to mitigate it.…”
Section: Fossil Fuel Communities and Climate Change Beliefsmentioning
confidence: 99%
“…Environmental challenges may serve as catalyzers of pro-environmental reflection and action. Experiencing a crisis prompts individuals to internalize and take action to ameliorate environmental problems ( McDonald-Harker et al, 2020 ). Problem-solving that results from effectively acting in response to environmental challenges is identified as adaptive actions, competency display, and societal development, within the framework of a PE ( Corral-Verdugo et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…As McDonald-Harker et al (2020) point out, children’s experiences of disasters not only provide researchers with a grasp of what children know in terms of content, but also how they experience this knowledge emotionally. In addition, beyond this capacity for acquiring knowledge and knowing, children affected by disasters are also capable of reflecting on this knowledge, confronting themselves and their attitudes in the light of their perceptions of change in their surrounding environment and recent experience of disasters.…”
Section: Emotions Children and Disastersmentioning
confidence: 99%
“…In addition, beyond this capacity for acquiring knowledge and knowing, children affected by disasters are also capable of reflecting on this knowledge, confronting themselves and their attitudes in the light of their perceptions of change in their surrounding environment and recent experience of disasters. Interviewing children aged between 5 and 17 and their parents, McDonald-Harker et al (2020) found that experiencing the floods in Alberta sparked their curiosity about what causes disasters, led them to investigate and think more about wider environmental issues, and encouraged them to take action on a micro level, engaging with their peers though fundraising campaigns in schools and sharing information with friends and family. Hence, although they are not always considered by practitioners or authorities (Walker et al, 2010), feelings and emotions play an important part in developing resilience, not just through positive emotions that promote adaptive behaviour in challenging situations, but also through emotions such as anger and fear that help children navigate and map a changing environment.…”
Section: Emotions Children and Disastersmentioning
confidence: 99%